Low-Dose Computed Tomographic Scans for Postoperative Evaluation of Craniomaxillofacial Fractures: A Pilot Clinical Study. Issue 2 (August 2020) - Elegbede, Adekunle; Diaconu, Silviu; Dreizin, David; Li, Guang; Dunlow, Ryan; Ngaage, Ledibabari M.; Rasko, Yvonne; Liang, Fan; Grant, Michael P.; Nam, Arthur J.
Abstract : Summary: Computed tomographic scans are frequently obtained following craniomaxillofacial fracture reconstruction. The additive radiation from such scans is not trivial; cumulative radiation exposure poses stochastic health risks. In this article, the authors postulate that a low-dose computed tomography protocol provides adequate image quality for postoperative evaluation of reconstructed craniomaxillofacial fractures. This study included patients for whom a computed tomographic scan was indicated following craniomaxillofacial fracture repair at a Level I trauma center. Postoperative craniomaxillofacial computed tomography was performed using a low-dose protocol, rather than standard protocols. A craniomaxillofacial surgeon and a radiologist interpreted the images to determine whether they were of sufficient quality. It was decided a priori that any inadequate low-dose computed tomography would require repeated scanning using standard protocols. The primary endpoint was the need for repeated computed tomography. In addition, the clarity of clinically significant anatomical landmarks on the images was graded on a five-point Likert scale. Twenty patients were scanned postoperatively using the low-dose protocol. Mean radiation dose (total dose-length product) from the low-dose protocol was 71 mGy · cm versus 532 mGy · cm for the preoperative computed tomographic scans that were obtained using conventional protocols ( p < 0.001). All 20 low-dose computed tomographic scans were determined to provide satisfactory image quality. No patients required repeated computed tomography secondary to poor image quality. Low-dose computed tomography received high image-quality scores. A low-dose computed tomography protocol that delivers approximately 7.5-fold less radiation than the standard protocols was found to be adequate for postoperative evaluation of craniomaxillofacial fractures. Larger prospective studies may be warranted. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.